Prevalence and sociodemographic determinants of selected noncommunicable diseases among the general population of Cyprus: A large population-based cross-sectional study - Kyprianidou, Maria; Panagiotakos, Demosthenes B.; Makris, Konstantinos C.; Kambanaros, Maria; Christophi, Costas A.; Giannakou, Konstantinos (My University, 2023)
Background: Noncommunicable diseases (NCDs) are the leading cause of morbidity and mortality worldwide. The aim of this study was to determine the prevalence of NCDs among the population of Cyprus and to identify the distribution of the socioeconomic and demographic determinants among individuals with the most frequent NCDs. Methods: A cross-sectional study was conducted using stratified sampling. Socioeconomic and demographic characteristics and the presence of NCDs were collected through a standardized questionnaire. The diseases were classified using the 10th revision of the International Classification of Diseases (ICD-10). Results: In total, 1140 individuals participated in the study, among whom 590 (51.7%) had at least one chronic disease. The most prevalent NCDs were hyperlipidemia (17.4%), hypertension (12.9%), and thyroid diseases (8.4%). We identified more males than females with hyperlipidemia aged 25–44 years old and >65 years old (p = 0.024), more males compared to females with hypertension (p = 0.001) and more females compared to males with thyroid diseases (p < 0.001). Individuals with hypertension and hyperlipidemia were more likely to be married, to have completed a higher education, and to have a high annual income. Discussion: In Cyprus, the majority of the general population had at least one NCD. Hyperlipidemia, hypertension, and thyroid disease are relatively common, even at younger ages, highlighting the need for the development of public health programs aimed at addressing and preventing NCDs.
Keywords: chronic diseases; hyperlipidemia; hypertension; noncommunicable diseases; prevalence